Effect of the 5-HT(4) receptor agonist tegaserod on the expression of GRK2 and GRK6 in the rat gastrointestinal tract - Nedi, Teshome (BMC Res Notes, 2018)
OBJECTIVE: Tegaserod is a 5-hydroxytryptamine type 4 (5-HT(4)) receptor agonist, formerly used in treating constipation predominant irritable bowel syndrome, which desensitizes 5-HT(4) receptors in rat oesophagus and colon in vitro. Desensitization of 5-HT(4) receptors is regulated by G-protein coupled receptor kinases. This study was designed to assess the effect of 5-HT(4) receptor activation on the expression of GRK2 and GRK6 in the rat oesophagus and distal colon by acute administration of tegaserod. RESULTS: Rats were treated with a single dose of tegaserod (5 mg/kg) and tissue samples of the oesophagus and distal colon were prepared and level of GRK2 and GRK6 protein expression was determined using western blotting. The immunodensity of GRK2 and GRK6 was normalized against the loading control β-actin and compared with control animals. Acute administration of tegaserod for 1, 2, 3, 4, 6, and 8 h did not change significantly the immunodensity of GRK2 or GRK6 in the oesophagus or GRK2 in the distal colon when compared with control animals. This may indicate that the basal level of GRK2 and GRK6 expression is sufficient to regulate the desensitization of 5-HT(4) receptors in acute drug treatment.